The Prevalence and Treatment Outcomes of Primary Tooth Injuries - Arikan, Volkan; Sari, Saziye; Sonmez, Hayriye (European Journal of Dentistry, 2010)
Objectives: The aim of the present study was to evaluate the type and prevalence of primary tooth injuries, as well as their treatment and treatment outcomes, among children referred to the Department of Pedodontics at the Ankara University Faculty of Dentistry in Turkey.Methods: The study population consisted of patients applying to the department with a primary tooth injury over a period of 21 months. Fifty-one patients presented with trauma to 99 primary teeth. Clinical and radiographic examinations were conducted on each patient. Age, sex, time, cause of injury, and number of teeth affected were recorded, and the type of trauma was identified according to Andreasen’s classification. The teeth were treated by one of the authors.Results: The majority of trauma occurred between the ages of 2 and 4. The most common type of injury was lateral luxation (33.3%). Most injuries (33.3%) presented during May. The most common form of treatment was follow-up only (39.4%), followed by extraction (29.3%) and root canal treatment (12.1%). The average follow-up period was 11 months. During the follow-up period, complications were observed in 4 teeth.Conclusions: The study results show that in the absence of acute symptoms, parents tend not to apply to a dental clinic for children’s injuries. This finding highlights the importance of informing the public about primary tooth injuries and their consequences. (Eur J Dent 2010;4:447-453)
Keywords: Dental trauma; Primary teeth; Prevalence; Treatment outcomes